Teratogenic Effect of Ciprofloxacin in Albino Rats - Zeinab Gazi (AlQalam Journal of Medical and Applied Sciences, 2021)
Aim. The present study aims to evaluate the risk of the ciprofloxacin drug on the development of fetuses of the albino rat during pregnancy. Method. Pregnant rats were exposed orally to 206 mg kg-1 of coumatetralyl daily on days 5 through 20 of gestation. Animals were sacrificed on the 20th day of gestation for fetal examination. Results. Ciprofloxacin produced a significant elevation in the percentages of late resorption sites and dead fetuses compared with the control group. The mean fetal weights were significantly reduced. Visceral abnormalities were revealed in the form of dilated brain ventricles, hypertrophy of the heart, hypoplasia of the lung, dilated renal pelvis. Skeletal examination showed wide open fontanel, incomplete ossification of parietal and interparietal bones, incomplete ossification of the sternum, reduction in the number, or even complete absence of phalanges, sacral, and/or caudal vertebrae. Conclusion. The results indicate that ciprofloxacin has a teratogenic effect at lower doses. Therefore, further studies are necessary to evaluate its safety during pregnancy.